Mechanisms of Variable p44 Expression by Anaplasma phagocytophilum - Lin, Quan (American Society for Microbiology, 2003)
The human intragranulocytic bacterium Anaplasma phagocytophilum promotes variation of P44s, which are surface-exposed proteins encoded by a p44 multigene family. In the present study, the specific p44 gene expression loci in four strains of A. phagocytophilum were identified and it was determined that each consisted of four tandem genes, tr1, omp-1X, omp-1N, and p44. A putative σ(70)-type promoter was found upstream of tr1. The p44 genes include a central hypervariable region flanked by conserved regions. The hypervariable region sequence in the p44 expression locus was duplicated and, regardless of the expression status, conserved at another locus in both low- and high-passage cell cultures of strain NY-37. No significant differences in the hypervariable region were found when we compared p44 sequences, at the level of cDNA, within the expression locus and within other loci in the genomes of strains NY-37 and HZ. Similarly, in cDNA isolated from patients and from assorted cultures of strains NY-31, NY-36, and NY-37, hypervariable regions of 450 deduced amino acid sequences of various p44s within each strain were found to be identical, as were those of p44 sequences in the genome of strain HZ. These data suggest that variations in p44 sequences at the level of the p44 expression locus occur through unidirectional conversion of the entire (nonsegmental) p44 hypervariable region including flanking regions with a corresponding sequence copied from one of the conserved donor p44 genomic loci. The data suggest that the P44 antigenic repertoire within the hypervariable region is restricted.